Omics Techniques (Genomics, Transcriptomics, Proteomics, and Metabolomics) in the Study of Oral and Systemic Biofilms - Jacinto, Rogério de Castilho [UNESP]; Rodrigues, Gladiston William Lobo [UNESP]; Oliveira, Laura Cesário [UNESP]; Gomes, Natalia Amanda [UNESP]; Ribeiro, Ana Paula Fernandes [UNESP]; de Moraes, Yuri Gabriel Chamorro [UNESP]; Dourado, Nayara Gabriely [UNESP] (Taylor & Francis, 2025)
The importance of omics methodologies in scientific research lies in their ability to provide an extensive and in-depth view of biological systems, allowing for the identification of molecular markers, resistance mechanisms, and potential therapeutic targets in biofilms associated with systemic and oral diseases. By enabling the integration and simultaneous analysis of different layers of molecular information, omics methodologies offer a more complete and precise understanding of the underlying biological processes, thus driving the discovery of new knowledge and innovations in the health field. This chapter explores the various omics techniques—genomics, transcriptomics, proteomics, and metabolomics, which are employed in the study of oral and systemic biofilms, and how these methodologies can be applied to uncover the complex interactions and structural dynamics within oral and systemic biofilms. By providing a comprehensive overview of the current state of omics techniques for research in biofilms, this chapter aims to emphasize the application of these technologies in understanding and combating biofilm-related infections, ultimately contributing to improved diagnostics, treatments, and preventive strategies in both oral and systemic health.